The Effect of Ni-TiO2 and Ni-TiO2-graphene Coatings and Heat Treatment Hardening on Solid Particle Erosion Resistance of Grade 410 Stainless Steel - KHALID, Wissam; AL-TAMEEMI, Hamza A. (Engineering Transactions, 2023)
Erosion by solid particles is a serious problem in many applications, especially in rotary machines with steel blades. Many coatings are currently being developed to improve erosion resistance. This study focuses on investigating the solid particles erosion (SPE) resistance of AISI 410 stainless steel and improving the SPE resistance using three different anti-wear techniques: hard coating (Ni-TiO2), hard coating with low shear resistance (Ni-TiO2-graphene) and hardening by heat treatment. The study also investigates the effect of different factors, including impact angle, jet pressure (particle speed) and solid particle type on each of the four types of specimens. The investigated anti-wear techniques improved the erosion wear rate by different percentages, such as 35.2% using Ni-TiO2 coating, 36% using Ni-TiO2-graphene, and 53.75% using heat-treatment when using silica sand, a 45° impact angle and a speed of 36.72 m/s were used. The results indicate a ductile erosion mechanism as the weight loss decreases with an increase in the impact angle. The investigated coatings were found to provide more stable erosion resistance under different impact angles. Surface roughness was reduced after SPE for coated surfaces, and surfaces showing a lower wear rate may not necessarily show less change in surface roughness. It was observed that deformation in the form of waviness only occurs when the surface is impacted by small rounded particles at a 45° angle. Wear rate parameters were calculated, which can be used to estimate the wear rate for the investigated material under various conditions.